2022
DOI: 10.3390/ph15111407
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab and Chemotherapy Combination Prolonged Progression-Free Survival in Patients with NSCLC with High PD-L1 Expression and Low Neutrophil-to-Lymphocyte Ratio

Abstract: The use of immune checkpoint inhibitors (ICIs) has provided overall survival (OS) benefits in patients with treatment-naïve advanced non-small cell lung cancer (NSCLC) without targetable driver mutations. However, studies comparing ICIs monotherapy with combination therapy either with chemotherapy or radiotherapy in programmed death-ligand 1 high expressors remain limited. This study aimed to retrospectively compare the treatment efficacy of the therapies by studying 47 patients with treatment-naïve advanced N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This allowed us to compare the effectiveness of chemotherapy and immunotherapy in each subgroup. In our previous study, which enrolled patients with high PD-L1 expression, a low NLR was found to predict improved PFS in patients receiving a combination of chemotherapy and pembrolizumab compared to those receiving pembrolizumab monotherapy ( 15 ). In this study, we further established that patients with a low NLR significantly benefited from improved PFS and OS when undergoing chemoimmunotherapy compared to chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed us to compare the effectiveness of chemotherapy and immunotherapy in each subgroup. In our previous study, which enrolled patients with high PD-L1 expression, a low NLR was found to predict improved PFS in patients receiving a combination of chemotherapy and pembrolizumab compared to those receiving pembrolizumab monotherapy ( 15 ). In this study, we further established that patients with a low NLR significantly benefited from improved PFS and OS when undergoing chemoimmunotherapy compared to chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has yet focused on the predictive role of NLR. Recently, we also established that a low NLR could predict the progression-free survival (PFS) benefit in NSCLC patients with high PD-L1 expression who received combination therapy compared to those receiving only ICIs ( 15 ). We hypothesized that NLR could also be a predictive biomarker for NSCLC patients with PD-L1 expression below 50%.…”
Section: Introductionmentioning
confidence: 99%
“…NLR as an easily measurable biomarker demonstrated to predict outcome in various cancers. Although a higher NLR was associated with poorer outcomes, there is no validated cut-off value distinguishing high from low, and therefore varies in literature [17,[24][25][26]. Recently Pham et al demonstrated a poorer OS for NLR ≥ 3 in 36 aRCC patients receiving ICI.…”
Section: Discussionmentioning
confidence: 99%
“…Although platinum + paclitaxel + pembrolizumab could prolong PFS, the median TFS was almost the same, and the incidence of severe TRAEs withdrawal was higher than that of chemotherapy alone. Therefore, the appropriate group of patients receiving combination therapy should be carefully selected [4].…”
Section: Pembrolizumab/ Keytrudamentioning
confidence: 99%